Optical absorption and luminescence studies of fast neutron-irradiated complex oxides for jewellery applications - Mironova-Ulmane, N.; Skvortsova, V.; Popov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We studied the optical absorption and luminescence of agate (SiO2), topaz (Al2[SiO4](F,OH)2), beryl (Be3Al2Si6O18), and prehnite (Ca2Al(AlSi3O10)(OH)2) doped with different concentrations of transition metal ions and exposed to fast neutron irradiation. The exchange interaction between the impurity ions and the defects arising under neutron irradiation causes additional absorption as well as bands’ broadening in the crystals. These experimental results allow us to suggest the method for obtaining new radiation-defect induced jewellery colors of minerals due to neutron irradiation.